To be present or not to be present: trials in absentia before the Special Tribunal for Lebanon - Gaeta, Paola (Journal of international criminal justice, 2010)
One feature of the Special Tribunal for Lebanon ( STL ) differentiating it from other international criminal tribunals (except for the Nuremberg International Military Tribunal) is that its Statute allows for trials in absentia. The Statute permits such trials when an accused failed to appear in court or even to appoint a defence lawyer, but only on the condition that, where the indictment could not be served or notified to the accused, it was duly publicized through the media or communicated to the state of residence or nationality of the accused. Following the case law of the European Court of Human Rights, Article 22(3) of the STL Statute allows for retrial, except where an absent defendant was represented at trial by counsel of his or her own choosing. The author argues this right to retrial should not be applied either where (i) the accused expressly waived in writing his right to be present, but then failed to appoint counsel of his choosing; or (ii) a state's failure to hand the accused over to the STL does not cure the accused's refusal to voluntarily surrender to the STL. She also argues that the right of retrial following trials in absentia ought to accrue to Lebanese courts, notwithstanding Article 5(1) of the Statute, which seems to prohibit Lebanese courts retrying individuals convicted by the STL. Finally, she takes into account the position of states that prohibit trials in absentia, but are requested to surrender a person convicted in absentia by the STL for the purpose of executing his sentence, suggesting an ad hoc agreement between the state in question and the STL may be required as a remedy